2017
DOI: 10.14417/ap.1198
|View full text |Cite
|
Sign up to set email alerts
|

Escala de Avaliação das Estratégias Sociais: Um estudo de validação com crianças em idade pré-escolar

Abstract: A Escala de Avaliação das Estratégias Sociais (EAES; Aguiar, 2007) destina-se a avaliar as estratégias sociais específicas que as crianças em idade pré-escolar utilizam nas tarefas sociais de entrada no grupo de pares, manutenção do jogo e resolução de conflitos. Neste estudo, avaliamos as características psicométricas dos dados obtidos com a EAES e com o Sistema de Avaliação das Competências Sociais (SSRS; Gresham & Elliott, 1990) em 349 crianças Portuguesas em idade pré-escolar. Internamente consistentes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Também muito utilizado em contexto de Psicologia Educacional até porque o seu público-alvo é do pré-escolar. Foi validado em Portugal por Fialho, & Aguiar (2017).…”
Section: Inteligência Socialunclassified
“…Também muito utilizado em contexto de Psicologia Educacional até porque o seu público-alvo é do pré-escolar. Foi validado em Portugal por Fialho, & Aguiar (2017).…”
Section: Inteligência Socialunclassified
“…Conflicts resolution was measured through the conflict resolution strategies subscale (6 items) of the Portuguese version of Social Strategies Rating Scale (SSRS; Beckman and Lieber, 1994;Fialho and Aguiar, 2017). The SSRS was administered to preschool teachers, who rated on a 5-point scale (1 = never, 3 = half of the time, 5 = almost always) how often the child uses social strategies during interactions with peers on preschool context.…”
Section: Social Competencementioning
confidence: 99%
“…Previous research on the predictors of social skills has reported positive effects of exposure to high-quality ECE classrooms (e.g., Curby at al., 2013), namely for children from low-income backgrounds (e.g., Burchinal et al, 2010). Also, studies investigating social skills have typically controlled for children's age (i.e., progression in social competence with age) and gender (i.e., boys generally scoring lower on social competence than girls) (e.g., Fialho & Aguiar, 2017;LaFreniere & Dumas, 1996), while others suggested variance in social skills as a function of language or verbal competence (e.g., Stephens et al, 2023). Importantly, despite the conceptual and empirical links between autonomy support and children's social skills development (e.g., Joussemet et al, 2005;Su-Russell & Russell, 2021), and the limited research, for instance, on the associations between child-centered classrooms and children's prosocial behaviors (e.g., Reio et al, 2002), to our knowledge, no studies have focused on the role of teachers' participation practices on children's social skills, nor investigated links between ECE teacher's practices, ECE quality, children's perceptions of participation, and children's developmental outcomes.…”
Section: Children's Social Skillsmentioning
confidence: 99%